Teori Manajemen Konflik - Alfian Ihsan Ramadhani; Dwi Putri; Helma Putri Kusuma; Muhammad Risqi; Tarisa Nabila Putri; Mu’alimin Mu’alimin (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Conflict is an unavoidable part of interactions between individuals and groups in an organization, including educational organizations. The way conflict is managed has a significant impact on organizational dynamics, both positively and negatively. This article aims to analyze various conflict management styles and conflict management methods used in resolving conflicts in educational organizational environments. Conflict management styles include five main approaches, namely competitive, collaborative, avoidant, accommodative, and compromise, each of which has its advantages and disadvantages. Meanwhile, conflict management methods, such as negotiation, mediation, arbitration, and team collaboration, are used to resolve conflicts systematically. The results of the analysis show that choosing the right conflict management style and method can minimize the negative impact of conflict and maximize opportunities for more innovative and effective solutions. In conclusion, effective conflict management is necessary to create a harmonious and productive organizational environment, especially in the education sector.